Semitic Genitive Constructions: an Expanded View - Kohēn, ʿErān (Journal of Semitic studies, 2019)
This survey is an attempt to bring together systematically all the main combinations of heads and attributes that together form the genitive constructions in Semitic. The paper demonstrates the extent of the Semitic genitive construction: in addition to its central role in the domain of the noun phrase, it is the preferred syntactic mechanism behind many phrase and clause types - syntactic adjectives and possessives (the pronoun *d_v¯ with an attribute), relative clauses, complex prepositions, prepositional phrases, gerundial forms and most types of adverbial clauses. It is the most important mechanism at the phrase level. The external syntax or syntactic function of the different constructions may be accounted for by the syntactic nature of the head as the grammatical centre of the entire construction. Accordingly, an adverbial head is naturally found heading an adverbial phrase or clause. In addition, there may be other, more complex factors: the fact that genitive constructions headed by pronouns also function as syntactic or analytic adjectives has to do with the nature of the adjective as a complex form that includes a pronominal element. The functional extent of the Semitic genitive constructions, in contrast with the often-limited adnominal use in other languages, deserves to be considered as a primary feature of the syntax of common Semitic.